Screening Sorghum Genotypes for Striga Resistance - Ardaly Abdou Ousseini; Mamadou Aissata Ibrahim; Fanna Maina; John Saviour Yaw Eleblu; Kwadwo Ofori (Journal of Agronomy Research, 2023)
In Niger, sorghum (Sorghum bicolor) is one of the most important staple crop for food and money. Despite the importance of the crop and its easiest adaptative capacity to dry, the crop is confronted to striga (Striga hermonthica), a plant parasite, which drastically hinder the productivity and causing yield loss between 20% to 80%. The best and easiest way to control and improve sorghum productivity is through the development of novel Striga resistance sorghum genotypes. The purpose of this study was to assess 20 sorghum genotypes from diverse country for striga resistance and grain yield capacity. Varieties with high yield average, medium size and resistance to Striga were found.
Keywords: Striga resistance